Universal newborn hearing screening in South Africa: a single-centre study. Issue 1 (18th March 2021) - Gina, Ayanda; Bednarczuk, Nadja F; Jayawardena, Asitha; Rea, Peter; Arshad, Qadeer; Saman, Yougan
Abstract : Hearing screening for newborn babies is an established protocol in many high-income countries. Implementing such screening has yielded significant socioeconomic advantages at both an individual and societal level. This has yet to permeate low/middle-income countries (LMIC). Here, we illustrate how newborn hearing screening needs to be contextually adapted for effective utilisation and implementation in an LMIC. Specifically, this advocates the use of auditory brainstem testing as the first-line approach. We propose that such adaptation serves to maximise clinical efficacy and community participation at a reduced cost.